Strategi Komunikasi Konseling Penyuluh Agama dalam Meminimalisir Perceraian di Kabupaten Aceh Singkil. - Gepeng Rambe; Zainun; Syawaluddin Nasution (PERSPEKTIF, 2023)
The purpose of this research is to analyze the causal factors and communication strategies of religious extension counselors to minimize divorce in Aceh Singkil District. This type of research is qualitative using an Islamic and sociological communication approach. The results of the study state that the factors that cause divorce: there is no harmony and responsibility; economic factors; education; moral crisis; presence of a third party; religious conversions; adultery; loveless marriage; domestic violence; underage marriage; ongoing quarrels and conflicts; developments or social media. Efforts to minimize divorce: planning marriage-age youth education, family counseling classes, and organizational meetings; guidelines for promoting sakinah families and resolving marital disputes; explain the laws of marriage in Islam; conduct counseling or premarital consultations; premarital courses as well as coaching for families and youth; carry out the sakinah family service center program (PUSAKA); fostering the activities of the taklim assembly or in certain recitations. The obstacles are: the location factor because it is too narrow in participating in fostering marriage and a sakinah family; the summary factor of the material and the time the guidance is delivered; the factor is the low education of religious instructors, the community still has an inherent understanding of customs; lack of training for religious instructors; there are still extension workers who do not master IT.